GAMIFIKASI DAN PLATFORM DIGITAL DALAM PENGEMBANGAN LITERASI ABAD 21 SISWA SMP - Munawaroh, Umu Nafisatul (Jurnal Buana Kata: Pendidikan, Bahasa, dan Ilmu Komunikasi, 2026)
This study aims to analyze the effectiveness of gamification and digital platform integration in enhancing 21st-century literacy among junior high school students in Indonesian language learning. The study is motivated by low student engagement, limited critical thinking skills, and inadequate digital literacy in secondary schools. A descriptive qualitative design was used, with data collected through classroom observations, teacher and student interviews, and analysis of digital learning documents. Findings indicate that gamification elements such as points, badges, levels, and challenges significantly increase students’ intrinsic motivation and engagement in reading and writing activities. The use of digital platforms, including Google Classroom, Quizizz, and digital text-based literacy, further strengthens students’ critical thinking, collaboration, creativity, and communication skills. The integration of both approaches creates an interactive, adaptive, and meaningful learning ecosystem. The study concludes that gamification and digital platforms serve as effective pedagogical strategies for addressing 21st-century literacy challenges, particularly in Indonesian language learning at the junior high school level.   Penelitian ini bertujuan untuk menganalisis efektivitas penerapan gamifikasi dan integrasi platform digital dalam meningkatkan literasi abad 21 peserta didik SMP pada pembelajaran Bahasa Indonesia. Latar belakang penelitian ini berangkat dari rendahnya keterlibatan belajar, kemampuan berpikir kritis, serta literasi digital siswa di sekolah menengah. Penelitian menggunakan desain kualitatif deskriptif dengan pengumpulan data melalui observasi kelas, wawancara guru dan siswa, serta analisis dokumen pembelajaran digital. Hasil penelitian menunjukkan bahwa elemen gamifikasi seperti poin, badge, level, dan tantangan meningkatkan motivasi intrinsik serta keterlibatan siswa dalam aktivitas membaca dan menulis. Penggunaan platform digital seperti Google Classroom, Quizizz, dan literasi berbasis teks digital juga memperkuat kemampuan berpikir kritis, kolaborasi, kreativitas, dan komunikasi siswa. Integrasi keduanya menciptakan ekosistem pembelajaran yang interaktif, adaptif, dan bermakna. Penelitian ini menyimpulkan bahwa gamifikasi dan platform digital merupakan strategi pedagogis efektif untuk mengatasi tantangan literasi abad 21, khususnya pada pembelajaran Bahasa Indonesia di SMP.